Aplicación del parámetro de rigidización para el análisis de impactos ambientales en playas turísticas del Atlántico (2021)
In the present investigation, the rigidity parameter, defined as the positive or negative contrast of the constructions or civil works present on the beaches, was applied to four (4) beaches in the department of Atlántico, which can alter the functioning of the ecosystem as satisfactory of the leisure and recreation needs. In this order, the rigidity perceived by the users and residents of the beaches, and the actual stiffening of these, were determined, also analyzing the environmental impacts associated with each of the beaches. As for the perceived stiffening, 74.1% feel benefited by the infrastructure of the beaches, 16.6% feel affected and the remaining 9.3% feel indifferent to such a situation. The case of real stiffening showed that only one (1) of the four (4) beaches is naturally disturbed and the remaining three (3) are minimally stiffened. Therefore, it is concluded that the use of the stiffening parameter is valid to evaluate levels of environmental impact on beach landscapes and also the level of satisfaction of beach users, as long as it is a complement to the Quality Index. Environmental in Tourist Beaches (ICAPTU).